Monitoring of the assortment structure and price dynamics of hepatoprotectors in the modern Ukrainian pharmaceutical market - I. O. Pukhalska; Аdaba Мukhamed; О. P. Hudzenko; О. L. Drozdov (Zaporozhye State Medical University, 2020)
High incidence of liver disease is one of the major problems for health care in the world. Today, etiotropics such as vaccines, antivirals, etc. are used to prevent and treat liver diseases. In addition, medicines for additional treatment of liver diseases, so-called hepatoprotectors, are often used in medical practice. Hepatoprotectors vary in both chemical composition and mechanism of action and target to increase liver resistance to adverse factors. The aim of the study was to provide a comprehensive analysis of Ukrainian pharmaceutical market in the framework of the group of hepatoprotectors and its price range. Materials and methods. The study was carried out grounding on the data provided by State Register of Medicines of Ukraine, International Classification of Diseases 11 issue (МКХ-11, ICD-11), entered into force on June 18, 2018 by the Order of Health Ministry of Ukraine № 892 dated 18.04.2019. "About Approval of the Eleventh Issue of the National Formulary of Medicines and Making It Available", National List of Essential Medicines, approved by the Cabinet of Ministers of Ukraine № 333 dated 25.03.2009 (on 07.05.2019), and analytical system of the pharmaceutical market "Farmstandard" by Morion company for the period between 2019 and the first half of 2020. During investigation, systemic, structural, logical practices and method of summarization were used. Results. The results of the research show that the domestic market for hepatoprotectors is saturated enough. It embraces both Ukrainian producers and foreign firms, mainly from India, Germany, France, Italy, China, Switzerland. The analysis of the changes in the prices for drugs of this group shows that during the period between 2017-2020 there was a significant increase in the prices of all drugs in the submitted sub-groups, which can be attributed to currency market instability. The structural analysis of the hepatoprotectors shows that the subgroup A05A X10, namely the combined drugs, constitutes the majority (57, 51, 67, 55 names according to studied year). The smallest subgroup is A05B A06 Ornithine oxyglurate (no names of medicine were registered by domestic producers in 2017). The activity of domestic producers should be noted. The proportion of Ukrainian preparations in this segment is 86.20 %, 84.12 %, 68.00 %, 56.79 % (first half of 2020) (according to years under consideration). Conclusions. The range analysis conducted for the period between 2017-2020 (first half-year) shows saturation of the domestic pharmaceutical market with hepatotropic drugs. Structural analysis conducted reveals that the pharmaceutical market in Ukraine is dominated by Ukrainian medicines, in particular from 56.79 % to 86.20 % (according to years under consideration). Price trend analysis shows low availability of imported products for some sub-groups: during 2019-2020, in sub-group A05A A02 Ursodeoxycholic acid price ranged from 1207.57 to 2376.15 UAH, and A05B A06 Ornithine oxyglurate it ranged from 1397.99 to 2557.55 UAH respectively.